HOW TO BUILD SELF-DIRECTED LEARNING READINESS (SDLR) AS THE FOUNDATION FOR NURSING STUDENTS TO BE LIFELONG LEARNERS? A SCOPING REVIEW - Anggia Astuti; Dodi Wijaya; Zainal Abidin; Rizeki Dwi Fibriansari (UNEJ e-Proceeding, 2023)
Background: Lifelong learning in nursing will be led to increased quality of education, development of nursing competency, and finally, increased quality of patient care. Nursing is a lifelong profession and Self-Directed Learning (SDL) is a valuable skill to remain relevant and productive professionals. Nursing students are expected to embrace SDL and develop these skills. This review aimed to discover determinant factors of Self-Directed Learning as a foundation for being a lifelong learner, Methods: The scoping review method adapted the Arksey and O’Malley framework. There were 11 out of 290 articles selected based on inclusion and exclusion criteria. Results: Self-Directed Learning Readiness built from three themes namely self-management, desire to learn, and self-control. Combining all the evidence, the results showed that SDL was shaped by internal factors (age, gender, self-efficacy, intelligence, desire, motivation, willingness to learn, level of education) and external factors (environment, learning opportunities, cooperation). In the SDLR method, the learning process changes from teacher-directed to learner-directed. Conclusions: Nursing institutions should provide the necessary resources to embrace SDL as a main-line teaching method to ensure competent lifelong professionals.